Word-forming semantics of nouns in denumerative word formation - Kostryba, Olha (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The relevance of the study is determined by the need to take into account the principle aspect in the analysis of the the word-forming system of the modern Ukrainian language. Scientific works testify that the derivatives motivated by noun-, adjective-, and verb-forming bases, which represent the core parts of the language, are considered for the most part.The purpose of the article is to establish the word-forming semantics of denumeratives – derived nouns grouped according to the nesting principle with vertex numerals belonging to the periphery of the forming base, find out the types of derivation and models of creation.The analysis was carried out using the structural-semantic method in combination with the use of lexical-semantic transformations.The onomasiological aspect involves the interaction of a simple motivational base, which is represented by adjectives, nouns, numerals, and verbs, and word-forming means; hence, thirteen word-forming meanings have been established, the carriers of which are simple substantives. The word-forming semantics of compound two- and three-base nouns, motivated by word combinations with subordinating and singly consecutive types of connection, have been determined; the number of word-forming meanings of complex formations is six. The nature of the correlation of the semantics of the formed word with the word-forming means was analyzed, particularly in syntagmatic word-forming meanings complicated by subcategorization and recategorization content, thus the types of derivation of word-forming meanings were established – mutational, modificational, and transpositional. Within each of the nineteen semantic positions of derivative substantives, one hundred and twenty-nine word-forming models were identified, presented in a descending order of their performance.The interpretation of the noun as a part of speech block in denumerative word formation contributes to the identification of the derivational capacity of the numerals of the modern Ukrainian language, complements the achievements of the principle derivation.